2019
DOI: 10.1101/19001925
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediagnostic breast milk DNA methylation alterations in women who develop breast cancer

Abstract: Background: Prior candidate gene studies have shown tumor suppressor DNA methylation in breast milk related with history of breast biopsy, an established risk factor for breast cancer. To further establish the utility of breast milk as a tissue-specific biospecimen for investigations of breast carcinogenesis we measured genome-wide DNA methylation in breast milk from women with and without a diagnosis of breast cancer in two independent cohorts. Methods: DNA methylation was assessed using Illumina HumanMethyla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…30 Studies have shown that aberrant DNA methylation often occurs in the early stages of cancer and persists throughout its development, and these aberrant DNA methylations have been found in a variety of tumors. 21,31,32 The methylation of cfDNA as a biomarker in the diagnosis of pulmonary nodules has also been studied. Li that the frequencies of APC and RASSF1A methylation were 24.1% and 43.1% in the plasma of lung cancer patients; however, the frequencies were 3.2% and 6.5% in benign lung disease.…”
Section: Cfdna Methylationmentioning
confidence: 99%
“…30 Studies have shown that aberrant DNA methylation often occurs in the early stages of cancer and persists throughout its development, and these aberrant DNA methylations have been found in a variety of tumors. 21,31,32 The methylation of cfDNA as a biomarker in the diagnosis of pulmonary nodules has also been studied. Li that the frequencies of APC and RASSF1A methylation were 24.1% and 43.1% in the plasma of lung cancer patients; however, the frequencies were 3.2% and 6.5% in benign lung disease.…”
Section: Cfdna Methylationmentioning
confidence: 99%